Proximal advantage in knowledge diffusion : the time dimension - Wang, Jue (2020)
This paper intends to explore the impact of geographic proximity on the diffusion of knowledge in the form of publication citations, and argues that codified knowledge is transmitted faster in proximity and is subject to similar geographic constraints as tacit knowledge. The geographic proximity advantage would be particularly relevant in the early stage of dissemination. We collected three sets of research articles published in 1990, 2000 and 2010 and compared the longitudinal citations they received domestically and from abroad. The study found that domestic citations accumulate faster and reach their peak much earlier than foreign citations, and the difference is most evident in the first few years after publication. The result shows that geographic proximity does play a role in the speed of knowledge diffusion and points to the network effect for citations. Those located closer to the knowledge origin would be exposed and react to publications faster due to the additional opportunities of research exchange and network.